Governing water in India : inequality, reform, and the state - Fernandes, Leela (University of Washington Press, 2022)
"Intensifying droughts and competing pressures on water resources foreground water scarcity as an urgent concern of the global climate change crisis. In India, individual, industrial, and agricultural water demands exacerbate inequities of access and expose the failures of state governance to regulate use. State policies and institutions influenced by global models of reform produce and magnify socio-economic injustice in this "water bureaucracy." Drawing on historical records, an analysis of post-liberalization developments, and fieldwork in the city of Chennai, Leela Fernandes traces the configuration of colonial historical legacies, developmental-state policies, and economic reforms that strain water resources and intensify inequality. While reforms of water governance promote privatization and decentralization, they strengthen the state centralized control over water through city-based development models. Understanding the political economy of water thus illuminates the consequent failures of the state within countries of the Global South"--